Management techniques for suppressing hogplum beetle by using some chemicals and cultural approach (Bangladesh Journal of Zoology, 2017)
Experiment on hogplum beetle, Podontia 14-punctata, was carried out to find out the suitable technique(s) for suppressing both larvae and adults of hogplum beetle. Results revealed in field trial that the highest mortality (98.56%) was found in all larval instars and adult stages of hogplum beetle after 24 hours by the effect of spading + Superior 505 EC (Chlorpyriphos + Cypermethrin) @ 10 ml/10 liter of water (T2) and lowest mortality was recorded in T3 (83.85%) treated leaves. The highest infestation reduction over control was obtained from T6 (62.75%) treated plant compared to other treated plants. In laboratory trial, the highest mortality (96.62%) was found in all larval instars and adult stages of hogplum beetle after 24 hours by the treatment of superior 505EC (T2) followed by T4 (88.00%) and lowest mortality was in T3 (69.70%) treated leaves. No mortality was observed in control treatment (T5).Bangladesh J. Zool. 44(2): 237-244, 2016